Seeds of the kingdom : utopian communities in the Americas - Peterson, Anna Lisa, 1963- (Oxford University Press, 2005)
This is a study of the experiences of two very different communities: former refugees in the mountains of El Salvador and Amish farmers in the Midwestern US. They both aim to embody the reign of God on earth, but from different perspectives. Both practical and ideological commonalities are described.